Prevention of Staphylococcus Epidermidis Biofilm Formation Using Electrical Current. Issue 2 (May 2014) - Del Pozo, Jose L.; Rouse, Mark S.; Euba, Gorane; Greenwood-Quaintance, Kerryl E.; Mandrekar, Jayawant N.; Steckelberg, James M.; Patel, Robin
A technique for the prevention of staphylococcal adhesion by electrical current exposure was investigated. Teflon coupons were exposed to a continuous flow of 10 3 cfu/ml Staphylococcus epidermidis with or without 2000 microA DC electrical current delivered by electrodes on opposite sides of a coupon, touching neither each other nor the coupon. A mean 3.46 (SD, 0.20) and 5.70 (SD, 1.03) log10 cfu/cm 2 were adhered to the non-electrical current exposed coupons after 4 h and 24 h, respectively. A mean 2.46 (SD, 0.31) and 1.47 (SD, 0.73) log10 cfu/cm 2 were adhered after 4 h and 24 h with exposure to 2000 microA electrical current delivered by graphite electrodes. A mean 2.21 (SD, 0.14) and 0.55 (SD, 0.00) log10 cfu/cm 2 were adhered after 4 h and 24 h with exposure to 2000 microA electrical current delivered by stainless steel electrodes. Electrical current may be useful in the prevention of staphylococcal adhesion to biomaterials.